Proliferation-proof Uranium/Plutonium and Thorium/Uranium Fuel Cycles: Safeguards and Non-Proliferation - Kessler, Günter (KIT Scientific Publishing, 2017)
Thermal and neutron physics analysis show that above certain concentrations of the isotope Pu-238 hypothetical nuclear explosive devices, made of reactor-grade plutonium, are technically not feasible. Future proliferation-proof fuel cycles are proposed which make use of methods of actinide tansmutation.Reactors operating in the thorium/uranium fuel cyce are loaded with <20% U-235 uranium fuel which can be made proliferation-proof against re-enrichment by adding a certain ppm level of U-232.